2010
DOI: 10.1039/c0md00108b
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning the designer drug ecstasy: non-psychoactive MDMA analogues exhibiting Burkitt's lymphoma cytotoxicity

Abstract: Burkitt's lymphoma (BL) is a particularly aggressive cancer that primarily affects African children. Unfortunately, effective and affordable treatment is out of reach of most of the afflicted. The illicit psychoactive drug methylenedioxymethamphetamine (MDMA, 'ecstasy') is cytotoxic to BL cell lines, but its low potency, psychoactivity and neurotoxicity preclude consideration as a therapeutic drug candidate. This paper describes the discovery of novel a-aryl analogues of MDMA that lack psychoactivity and reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…The receptor and transporter binding assays performed in the current study targeted only the receptor/ transporters to which racemic MDMA was shown to display affinity in a previous experiment performed by our group (Gandy et al, 2010). Even though MDMA did not display high affinity at 5-HT 1A receptors in that experiment, we have nevertheless performed 5-HT 1A receptor binding for both enantiomers, as it has been suggested that MDMA's antidyskinetic effect involved a 5-HT 1A -mediated mechanism .…”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“…The receptor and transporter binding assays performed in the current study targeted only the receptor/ transporters to which racemic MDMA was shown to display affinity in a previous experiment performed by our group (Gandy et al, 2010). Even though MDMA did not display high affinity at 5-HT 1A receptors in that experiment, we have nevertheless performed 5-HT 1A receptor binding for both enantiomers, as it has been suggested that MDMA's antidyskinetic effect involved a 5-HT 1A -mediated mechanism .…”
Section: In Vitro Pharmacologymentioning
confidence: 99%
“…A companion study shows that the most active compound versus lymphoma cells from Series 1 (compound 6) and two of the even more active ones from Series 2 (compounds 16 and 17) are in fact less toxic than MDMA to SH-SY5Y: a catecholaminergic neuroblastoma cell line that is used to model MDMA neurotoxicity. The same study also shows compound 6 having diminished psychoactivity when compared with MDMA in the prepulse inhibition of the acoustic startle reflex test in Wistar rats [11]. Furthermore, in the present study, while constituent cells of derived lines from all B-cell malignancies proved susceptible to one or more of the analogues tested, the relative level of sensitivity to a given compound could be quite different depending upon the cell line targeted indicating a degree of selectivity in the compounds' actions against lymphoma cell subtypes.…”
Section: Discussionmentioning
confidence: 65%
“…Screening against the sensitive L3055 cell line revealed no significant difference in the cells' response to compounds containing α-subsituents with either different steric (13)(14)(15)(16)(17) or stereoelectronic (9)(10)(11)(12) properties. Instead, the addition of further aromatic rings, thereby increasing the size of substituents at the α-carbon of MDMA, appeared a unifying factor to increasing potency: i.e.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations